Online journalism : - Craig, Richard (Thomson, 2005)
Online journalism reporting, writing, and editing for new media is the first truly comprehensive textbook available that can teach students how to report, write, and edit strictly for online media. Unlike other texts that simply "tweak" traditional writing and editing techniques, ONLINE JOURNALISM was created specifically with the Internet in mind. Written in a lively style, this book will appeal to students who want to explore writing opportunities with online media. It is also supplemented by an in-depth Web site that provides links to relevant current stories and sound clips of interviews with professionals.